West African sorghum beer fermented with Lactobacillus delbrueckii and Saccharomyces cerevisiae: shelf‐life and consumer acceptance. Issue 3 (17th June 2019) - Djameh, C.; Ellis, W. O.; Oduro, I.; Saalia, F. K.; Blay, Y. M.; Komlaga, G. A.
Abstract : The fermentation profiles, shelf‐life and consumer acceptance of traditional West African sour sorghum beer ( pito ) fermented with pure commercial starter cultures of lactic acid bacteria ( L. delbrueckii) and yeast ( Saccharomyces cerevisiae ) were evaluated. The beers from this 'pure culture' approach were compared with the spontaneous fermentation of pito wort. Lactic acid formation, pH change and extract utilisation were monitored during fermentation. Lactic acid content was used as a measure of sourness to establish the spoilage level of over‐sourness. Further, regression models relating sourness to the time the drink was kept were used to predict the shelf‐life. Consumer acceptance of the product was evaluated using a novel nine‐point hedonic scale. The pure culture and traditionally fermented beers followed similar lactic acid and fermentation profiles but strain‐specific differences were observed. Similar levels of pH, lactic acid level and extract utilisation were achieved. An improvement in shelf‐life of two days was found over traditionally fermented pito . There was no statistical difference between the two pito products for overall liking and taste. However, there was a preference for the aroma of the pure culture pito . It is suggested that the use of pure cultures will facilitate the scale‐up of pito production. © 2019 The Institute of Brewing & Distilling